Milage app: mobile learning of mathematics - Figueiredo, Mauro (2017)
This paper presents the novel app MILAGE Learn+ Launcher for smartphones and tablets where students can solve mathematical problems outside the classroom or at home and increase the time they spend learning and practicing mathematics. This app is a tool for learning mathematics that provides a set of problems organized according to the curriculum. It was designed for upper secondary schools but it can be used for other levels and subjects too. This tool is innovative in the introduction of self and peer evaluation for students of secondary schools in a gamification process of solving problems. With this app students solve mathematical problems and they have immediate feedback that is used for self-evaluation. After solving the problem and doing the self-evaluation the student can choose to watch a concise or detailed video to study the problem resolution. The concise video shows the steps need to solve the problem. The detailed video shows in more detail, including background information that may help low achiever students understand the resolution of that problem. In this way, the student can watch the video as many times as those needed to learn how to solve that problem. This is a step for the inclusion of low achiever students in the process of learning mathematics. This app also provides three levels of problems: beginners, intermediate and advanced to accommodate the low achievers and also motivate top performers students to use the app. The student can also at anytime evaluate his peers. In this way, the student can also study again problems of a certain topic when he is evaluating the resolution of a problem solved by another student. In this way, the teacher can also check the self and peer evaluation of his students and has feedback about students’ achievements.